Supratentorial cavernous haemangiomas and epilepsy: a review of the literature and case series. Issue 5 (1st May 1999) - Moran, N F; Fish, D R; Kitchen, N; Shorvon, S; Kendall, B E; Stevens, J M
Abstract : OBJECTIVES: To characterise the clinical features and response to treatment of supratentorial cavernomas associated with epilepsy. METHODS: A systematic review of the literature was carried out and a retrospective case series of patients with cavernoma diagnosed by MRI and/or histology was compiled. Patient selection biases in the literature review were reduced as far as possible by selection of unbiased publications. RESULTS: In the literature, cavernomas were relatively less common in the frontal lobes. There were multiple cavernomas in 23% of cases. The main clinical manifestations were seizures (79%) and haemorrhage (16%). The annual haemorrhage rate was 0.7%. The outcome after excision was good with improvement in seizures in 92% of patients. In the case series the surgical outcome was less favourable, reflecting inclusion of a higher proportion of patients with intractable epilepsy. In both the literature review and the case series, outcome was poorer in cases with a longer duration of seizures at the time of surgery. CONCLUSIONS: The good surgical results, particularly in cases treated earlier, and the significant cumulative haemorrhage rate, suggest that excision is the optimum treatment. However, these factors have not been examined prospectively and, despite the availability of several retrospective studies, the optimum treatment, particularly for non-intractable cases, will only be determined by a prospective study.